Assessment of the Relationship between Y-Balance Test and Stabilometric Parameters in Youth Footballers. (16th November 2020) - Sikora, Damian; Pałac, Małgorzata; Myśliwiec, Andrzej; Wolny, Tomasz; Linek, Paweł
Abstract : Objectives . The purpose of the study was to evaluate the correlation between dynamic test results obtained on a stabilometric platform and the results achieved on the Y-balance test (Y-BT). Method . The study group consisted of 52 adolescent athletes, aged 14 to 17 years. Each participant was evaluated in the scope of their ability to maintain dynamic balance using the Y-BT as well as via dynamic tests on the 'Alfa' stabilometric platform. The following parameters were analysed: (a) from the Y-BT—relative reach of the right and left lower limbs in the anterior, posterolateral, and posteromedial directions, as well as the side-to side difference in relative reach for each direction and (b) from the 'Alfa' platform—path length and time to reach the target using right and left lower limbs in the anterior and posterior directions. Results . A correlation between the results obtained on the stabilometric platform and the Y-BT was found only for the posteromedial direction. Statistical analysis demonstrated that the increased difference between the right and left lower limbs in the posteromedial test is related to an increase in time taken to reach the points located forward and to the left, and backwards and to the right, as well as an increase in the overall time required to complete the task on the stabilometric platform. Conclusions . The results from the Y-BT and stabilometric platform are weakly related in adolescents. These findings indicate that the Y-BT and stabilometric platform analyse different kinds of dynamic balance in adolescents. Thus, these tools should not be used interchangeably in clinical practice or scientific research.